Chicken soup for the Christian soul : 101 stories to open the heart and rekindle the spirit - Canfield, Jack, 1944- (Deerfield Beach, Fla. : Health Communications, 1997)
These stories will deepen readers' Christian faith & expand their awareness of how to practice Christian values in their daily life: at home, at work & in the community. This collection will open readers' hearts to the experience & expression of more love in their lives. This collection will open your heart to the experience and expression of more love in your life and will remind you that you are never alone or without hope, no matter how challenging and painful your circumstances may be.
Keywords: Christian life -- Anecdotes